Health Financing and Policy: A Comprehensive Literature Review - Muhammad Alwy Arifin; Muh. Yusri Abadi (Yayasan Sinergi Kawula Muda, 2024)
Health financing and policy are critical components in shaping the accessibility, quality, and sustainability of healthcare systems worldwide. This literature review synthesizes existing research on health financing models and policies, exploring their impact on health outcomes, equity, and system efficiency. The review identifies key financing mechanisms, including taxation, social health insurance, and out-of-pocket payments, and examines the policy frameworks that guide their implementation. Furthermore, it discusses the challenges of financing health care in low- and middle-income countries (LMICs) and the implications of global health financing initiatives. The findings underscore the need for adaptive policy strategies that align with the evolving dynamics of health systems and financial sustainability.